Fauna and landscape-zonal distribution of Orthoptera in the Komi Republic (Russia) - O.I. Kulakova; A.G. Tatarinov (Кавказский энтомологический бюллетень, 2020)
Orthoptera is a promising model group of insects for large-scale zoogeographic studies. The Komi Republic (Russia, West Siberia) is a suitable region for such kind of work, because it has meridional orientation, coinciding with the global trend of biodiversity, and a well-defined natural latitudinal zonation (from the southern taiga to the southern tundra). The goal of the article is to describe a general composition of the orthopteran fauna and to characterize landscape-zonal distribution patterns of species in the Komi Republic. This work is based on data collected by the authors from 1990 until 2018 in 72 geographical localities. In Komi Republic, 29 species of Orthopetra from three families and 18 genera occur. Acheta domesticus (Linnaeus, 1758), Gryllotalpa gryllotalpa (Linnaeus, 1758) are synanthropic species in the region. The family Acrididae with 18 species is the most diverse group of Orthoptera in the region. Tettigoniidae with 7  species is in the second place, and the family Tetrigidae (4 species) is in the third one. Species richness of Orthoptera gradually but significantly decreases northwards: from 28 species in the southern boreal forests to 6 species in the tundra. Trans-Palaearctic species dominate in longitudinal direction and polyzonal species lead in latitudinal direction. Ranges of some species are expanded due to anthropogenic habitats. In the last two decades, active expansion has been observed in Phaneroptera falcatа, Omocestus haemorrhoidalis, Stenobothrus lineatus, Aeropedellus variegatus. These species extend to the north of the taiga zone along highways, railways and linear communications (oil and gas pipelines, power lines) that almost diagonally cross the territory of the republic.